Network analysis of inter-country export patterns in the EU - Rašković, Matevž (Teorija in praksa, 2015)
We employ a network analysis approach to study inter-country export patterns of EU member states. We employ three weighted centrality measures to analyse the importance of individual member states in the network. We focus specifically on so-called small states and their structural importance in the network. By employing weighted generalised blockmodeling, we identify five specific blocks of countries. Network visualisations further show a strong core-periphery structure in our network, as well as two specific groups of countries with higher relative intra-group trade (called cliques in network analysis). Our results offer important implications for the theory of export patterns of small states and show that small states do not necessarily focus their exports more on neighbouring markets compared to large states.
Keywords: analiza omrežij; economics; ekonomija; EU; European Union; Evropska unija; exports; foreign trade; izvoz; zunanja trgovina